(untitled) (Journal of the College of Basic Education, 2023)
The land of Iraq is the cradle of civilization and the source of science, culture and urbanization.This ancient country is home to the original ancient civilizations, which left their imprints on the civilizations ofall of humanity.The first invention of writing was in the year 3200 BC in Iraq, when writing appearedIn the era of civilization (Jamdet Nasr), one of the roles of civilization in the Aridain Valley, as providedcivilizations (Sumerian, Assyrian, and Babylonian) with many translations and epics that were foundIt is in the library of King Ashurbanipal, where that library contained thousands (clay figures).which included various subjects (scientific, literary, and military), the most prominent of which was theThe original (Epic of Gilgamesh). Schools in ancient Iraq circulated texts among themselves.The schooling of school students, all of this testifies to the culture of the people of Iraq and their impact on humanity.In Islamic times, the city of Baghdad became a beacon of knowledge and a meeting place for scholars.writers and poets, and a center for translation, which has been exposed to the scientific and cultural movementIn Iraq, the setback occurred in the year 1258 AD, during its invasion by the Mongol colonialists, and what followedTo the year 1968, when a specialized geographic region emerged within the main commercial areaThe city of Baghdad (C.B.D), which is the Al-Sari area, which has become a meeting place for scholars and writers.Poets, writers, journalists, intellectuals and politicians are in the streets of this area (sari,Al-Mutanabbi and Al-Qishla) from all over the country, which is a remarkable geographical phenomenon.where people (with books, magazines, newspapers, printing and reproduction tools, and science materials)and culture) that constructive dialogue is an exciting sight every day in this geographical area, and on FridayMore exciting than that.